Effect of Ficus carica leaves Aqueous Crud Extract on the Number of Wild Fruit Flies and Sperm Morphology of Laboratory Albino Male Mice - Ahmed, Mahmood Othman (Sulaimani Journal for Pure and Applied Sciences, 2023)
The purpose of this study was to compare the effects of two concentrations of aqueous crude extract from Ficus carica leaves on fruit fly numbers, sex ratios, and generations, as well as laboratory albino mouse sperm abnormalities. Fruit flies were given the concentrations of 1% marked as C1 and 2% marked as C2 in culture media and allowed to complete their life cycle at an acceptable temperature (25o C±2) in an incubator. Same concentrations were given to the tested mice in drinking water. Each treatment consisted of five replications, with untreated mice and flies serving as the control groups. Fruit fly findings were seen in the first and second generations, and mouse sperm morphology was examined one month following treatment. The results revealed that tested concentrations had no significant impact (P≤0.05) on the quantity of fruit flies mean values were (40.650 ± 2.40 5and 39.250 ± 2.624) froe first and second concentrations compared to 34.550 ± 2.12 in control group, but they did have a significant impact (P≤0.05) on the sex ratio (shifted toward females (40.733 ± 1.969) in comparison to males (35.566 ± 1.838), least significant differences(L.S.D.) were = 5.148, and generation-concentration interactions, the highest number were recorded was females in second generation (42.900 ± 2.203). The treated mice showed Significant effect of concentrations on sperm without tail and highly significant effect (P≤0.01) on sperm without hook (mean values were 5.6 ± 0.37 and 2.0 ± 0.44 in high concentration while in control group the values were 2.0 ± 0.44 and1.0 ± 0.44) for both aberrations respectively. Our results clearly indicated change in sex ratio among treated fruit flies and induction of some morphologic changes in mice sperms after treatment of fig leaves aqueous crud extract.
Keywords: Fig leaves extract; Drosophila melanogaster; Sex ratio; sperm abnormalities